2005
DOI: 10.1590/s1413-86702005000300009
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic encephalopathy in dengue shock syndrome: a case report

Abstract: Dengue fever is the most important arboviral infection in the world, with an estimated 100 million cases per year and 2.5 billion people at risk. Encephalopathy is a rare complication of dengue virus infection and may occur as a consequence of intracranial hemorrhage, cerebral edema, hyponatremia, cerebral anoxia, fulminant hepatic failure with portosystemic encephalopathy, microcapillary hemorrhage or release of toxic products. We report a rare case of hemorrhagic encephalopathy in dengue shock syndrome cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 6 publications
2
22
0
1
Order By: Relevance
“…Our observation concurs with previous findings of cerebral [8,9] and macular haemorrhages [10] in patients with acute dengue infection. We highlight the importance of recognising dengue infection in patients who present with strokelike episodes, and who originate from countries where dengue is endemic.…”
supporting
confidence: 93%
“…Our observation concurs with previous findings of cerebral [8,9] and macular haemorrhages [10] in patients with acute dengue infection. We highlight the importance of recognising dengue infection in patients who present with strokelike episodes, and who originate from countries where dengue is endemic.…”
supporting
confidence: 93%
“…In Brazil, atypical manifestations of dengue infection, such as hepatitis, myocarditis and encephalitis, have been observed during epidemics that occurred in Ceará in 1994, in the state of Pernambuco in 1997 and in Campos in 2005 [4,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the majority of dengue cases did not fulfi ll all the criteria for DHF/DSS and dengue was confi rmed only after autopsy completion. In the literature, such cases are usually described as atypical manifestations, published as separate reports, or described as exotic fi ndings after autopsies (27) We found that patients aged >65 years had a high possibility of death, which may be related in part to the high frequency of comorbidities reported in the elderly (38) (39) (40) (41) (42) (43) (44) . Information on comorbidities is not included in the Brazilian Information System for Notifi able Diseases, and this information is obtained only through investigation of fatal dengue cases (40) (42) .…”
Section: Discussionmentioning
confidence: 77%